Impact of oceanographic gradients and marine heatwaves on the picophytoplankton community in the Northern California Current System - Kristin E. Forgrave; Carey P. Sweeney; Melissa Steinman; Anvita U. Kerkar; Timothy M. Pettit; Anne W. Thompson (Frontiers in Marine Science)
The Northern California Current (NCC) system is a productive coastal ecosystem with a mosaic of temporal and spatial features. The phytoplankton community plays a crucial role in supporting the rich ecosystem and economically important fisheries of the NCC. Our study integrates data across two years (2022-2023) and multiple transects to investigate the community composition of two major phytoplankton groups in the NCC: picocyanobacteria and photosynthetic picoeukaryotes (PPE). The abundances and cell sizes of the phytoplankton were measured using flow cytometry. We found PPE present at similar concentrations in both summer and winter, while picocyanobacteria were much more abundant in the summer than the winter. The relationship between the picocyanobacteria and PPE varied across on- to off-shore transects with different coastal bathymetry. Abundances of both picophytoplankton increased with distance from shore. Cell size also varied along these gradients. Sampling during a marine heatwave in summer 2023 revealed a shift towards smaller picophytoplankton. Overall, these data reveal a dynamic microbial community underlying a productive coastal system, which could inform management decisions and future ecosystem models in the context of climate change and marine heat waves.